Особняк с выходом в астрал: роман / Татьяна Полякова - Полякова Татьяна Викторовна (Авантюрный детектив, 2021)
Экземпляры: (20220128) / Инвентарный номер: 35389 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-44